2021
DOI: 10.1001/jamanetworkopen.2021.38926
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antimicrobial Prophylaxis With Double-Dose Cefuroxime and Surgical Site Infections in Patients Weighing 80 kg or More

Abstract: IMPORTANCE Many guidelines recommend a weight-adopted dose increase of cefuroxime for surgical antimicrobial prophylaxis (SAP). However, the evidence that this approach is associated with lower rates of surgical site infection (SSI) is limited.OBJECTIVE To assess whether double-dose cefuroxime SAP was associated with a decreased SSI rate in patients weighing at least 80 kg. DESIGN, SETTING, AND PARTICIPANTS This cohort study included adult patients (>18 years)weighing at least 80 kg who underwent 9 major surgi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Although our primary exposure variable was the exact timing of SAP administration, our data confirm findings from many previous studies that other confounders are significantly associated with SSI risk: higher ASA score, clean-contaminated wound classes (vs clean), and surgical procedures exceeding standard time were associated with an increased risk, as shown elsewhere. The duration of the surgical procedure can be impacted by intraoperative complications that may further affect the healing process and increase the risk for SSI.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Although our primary exposure variable was the exact timing of SAP administration, our data confirm findings from many previous studies that other confounders are significantly associated with SSI risk: higher ASA score, clean-contaminated wound classes (vs clean), and surgical procedures exceeding standard time were associated with an increased risk, as shown elsewhere. The duration of the surgical procedure can be impacted by intraoperative complications that may further affect the healing process and increase the risk for SSI.…”
Section: Discussionsupporting
confidence: 88%
“…The RCT may have been confounded, as a higher dose of SAP for patients with a body weight above 80 kg was introduced during the study period, which could have interacted with the timing windows. Nonetheless, a recent study by our group demonstrated that doubling the dose of cefuroxime in most surgical procedures does not decrease SSI rates. In addition, the RCT was stratified by center and may have been confounded by differences between the 2 participating centers (eg, different case mix as well as experience and skills of surgical staff).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations